KEMAMPUAN PENGUASAAN MAJAS PERTENTANGAN SISWA KELAS XII SMK KESEHATAN SAHATA KOTA PEMATANGSIANTAR - Dedi Zulkarnain Pulungan (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2014)
Figure of speech CONFLICT CONTROL CAPABILITIES HEALTH CLASS XII SMK SAHATA  CITY  PEMATANGSIANTAR   LESSONS  YEAR  2014-2015  DEDI ZULKARNAIN  Pulungan  NIM  :  8136192007  FIELD  STATE  UNIVERSITY GRADUATE  INDONESIAN  ABSTRACT  The  research  was  conducted  in  SMK SAHATA  Health  Academic  Year  2014-2015  100  City  Road  Melanthon  siregar Pematangsiatar.dengan  penelitain  Methods  Descriptive  .  This  study  aimed  to describe the ability of opposition figure of speech in a sentence mastery  class XII student of SMK HEALTH SAHATA Pematangsiantar 2014-2015 academic year of calculation of the percentage figure of speech known mastery ability opposition in class XII student sentence quite able to value - average ( mean ) 70.33 . Students were categorized memproleh value (A) there is as much as 33.33 % gain value (B) there is as much as 26.67 % , gain value (C) there is as much as 20 % , memproleh value (D) there are as many as 20 % and category value (E) there as much as 0 % .From the results of the analysis of data and the number of students who meet the criteria of completeness of the results of the ability to master figure of speech in a sentence contradictions exist in both categories with the amount of 80 %. Keywords : Mastery opposition figure of speech